Immunoglobulin M biosynthesis. Production of intermediates and excess of light chain in mouse myeloma MOPC 104E - Parkhouse, R. M. E. (1971)
Immunoglobulin M (IgM) biosynthesis was studied with mouse plasma-cell tumour MOPC 104E as a model system. Cell suspensions prepared from solid tumours were incubated in vitro with [(3)H]leucine; the radioactivity incorporated into intracellular and secreted proteins was analysed by sucrose-density-gradient centrifugation and polyacrylamide-gel electrophoresis. The tumour secretes IgM and light chains. `Pulse–chase' experiments indicated average secretion times of 1.5h for light chain and 2.5h for IgM. The order of disulphide-bond assembly within the cell was shown to be heavy chain+light chain → heavy chain–light chain intermediate → IgMs. The 7S subunit (IgMs) was polymerized into IgM just before or at the time of secretion. Measurements of heavy-chain/light-chain radioactivity ratios in intracellular HL and IgMs and secreted IgM demonstrated the existence of a light-chain pool participating in IgM biosynthesis. The size of the light-chain pool, together with analysis of clones isolated in vivo, suggested that the tumour contains cells in which light-chain synthesis is in excess of heavy-chain production.